How and why funders support engaged research - Angela T. Bednarek; Ben Miyamoto; Kristin Corbett; Charlotte Hudson; Gayle Scarrow; Maeghan Brass; Kim DuMont; Bev Holmes; Lauren Supplee; Robert McLean; Jaspal Bhatia; Shamira Chappell; et al. (Proceedings of the National Academy of Sciences, 2025)
Research that better aligns policy, practice, and research communities is gaining momentum around the world. This includes engaged research strategies that bring partners, and their diverse perspectives and kinds of knowledge, together to shape research agendas with on-the-ground-needs and to create dynamic problem-solving processes. These approaches aim to generate more equitable and effective solutions to societal challenges. Although many of these partnered strategies have a longstanding history, entrenched research cultures, practices, and institutional structures stand in the way of scaling them. Given the outsized role funders play in shaping research efforts, funders are a critical lever for change. This perspective describes the efforts of a global collaborative of philanthropic and public funders who are adapting their practices, supporting the development of infrastructure (e.g., capacity-strengthening, facilitation expertise, processes to guide relational work, etc.), and targeting system-level challenges to enable engaged research to maximize its potential. The authors integrate insights from different issue areas, geographies, and funding areas to provide concrete examples of funder activities that support engaged research and to suggest areas for further action. Recommendations include scaling changes in funding practices, deepening understanding of how and when engaged research leads to improved outcomes, and reshaping how success is defined and measured.